Pemetaan Habitat Burung Air Berdasarkan Analisis Citra Satelit di Hutan Mangrove Cagar Alam Pulau Dua, Banten - Helen Atmisuri; Enggar Utari; Indria Wahyuni; Hartanto Sanjaya (Jurnal Planologi, 2023)
Waterbirds are birds that live around the coast that use migration sites to carry out life activities. This research was conducted in 2022, aiming to determine the condition of waterbird habitat, mapping waterbird habitat, and the relationship between the results of satellite imagery analysis and the presence of waterbirds in the mangrove forest of Pulau Dua Nature Reserve. The research method used is the point count or index point of abundance (IPA) method to determine the habitat conditions of waterbirds and remote sensing methods using Google Earth Engine (GEE) satellite imagery. The results of the study showed that waterbirds are mostly active in wetland areas. The mapping results from the MNDWI (Modified Normalized Difference Water Index) analysis obtained negative results because the detected land is not a body of water and the surrounding area is overgrown with vegetation, it can be said that the results are negative due to air mixing with other objects. Mapping results from MSAVI (Modified Soil Adjusted Vegetation Index) analysis were obtained with a range of 0.3-0.4 which indicates moderate vegetation conditions. The correlation result of the water presence (MNDWI) with the presence of waterbirds have a value of r = 0.944 belong to the category of very strong relationship and the correlation result of the land presence (MSAVI) to the presence of waterbirds have a value of r = 0.537 belong to the category of strong relationship too. The results of this study can be implemented in education in the form of material analysis using KD. 3.10 and KD. 4.10 class X high school. Keywords: Google Earth Engine, Pulau Dua Nature Reserve, and Waterbird Habitat